INFLATION RATE, INTEREST RATE ON BANK INDONESIA CERTIFICATES AND GROSS DOMESTIC PRODUCT ON THE COMBINED STOCK PRICE INDEX - Negara, Andi Kusuma; Nugrohojati, Erni Agung (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
The purpose of this research is to obtain empirical evidence of the influence of the inflation rate, interest rates on Bank Indonesia Certificates (SBI) and Gross Domestic Product (GDP). The independent variables used are inflation, SBI interest rates, and Gross Domestic Product (GDP). The dependent variable used is the Composite Stock Price Index (IHSG) policy. In this study, the macroeconomic factors used were the inflation rate, SBI interest rates and GDP. The data taken is the monthly closing price of each dependent and independent variable. The sampling method is 60 months of closing price data. The data used is secondary data with documentation data collection methods. The analytical tool used is multiple linear regression. The partial results of the study show that only GDP has a significant effect on the JCI on the IDX, while the inflation rate and SBI interest rates do not have a significant effect on the IHSG on the IDX. And simultaneously shows that the inflation rate, SBI interest rates and GDP have a significant effect on the IHSG on the IDX. Keywords: JCI, inflation rate, SBI interest rate, GDP. The purpose of this research is to obtain empirical evidence of the influence of the inflation rate, interest rates on Bank Indonesia Certificates (SBI) and Gross Domestic Product (GDP). The independent variables used are inflation, SBI interest rates, and Gross Domestic Product (GDP). The dependent variable used is the Composite Stock Price Index (IHSG) policy. In this study, the macroeconomic factors used were the inflation rate, SBI interest rates and GDP. The data taken is the monthly closing price of each dependent and independent variable. The sampling method is 60 months of closing price data. The data used is secondary data with documentation data collection methods. The analytical tool used is multiple linear regression. The partial results of the study show that only GDP has a significant effect on the JCI on the IDX, while the inflation rate and SBI interest rates do not have a significant effect on the IHSG on the IDX. And simultaneously shows that the inflation rate, SBI interest rates and GDP have a significant effect on the IHSG on the IDX. Keywords: JCI, inflation rate, SBI interest rate, GDP.